2006
DOI: 10.2460/javma.229.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ilial screw loosening after triple pelvic osteotomy in dogs: 227 cases (1991–1999)

Abstract: TPO screw loosening was multifactorial and related to stability of the affected ilium, screw type, and screw position. Placing cancellous screws that do not engage the sacrum in pelvic osteotomy plate positions 1 through 3 may decrease the number of screws that loosen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 17 publications
0
44
0
1
Order By: Relevance
“…The mean estimate of SI change was higher with DCP than with LPS or dLPS but the variability rendered non‐significance. It has been suggested that increased screw purchase can be obtained by engaging the sacrum through the ilium when applying a lateral bone plate in dogs, especially after pelvic osteotomy . Increased bone purchase might lead to less pelvic canal narrowing.…”
Section: Discussionmentioning
confidence: 99%
“…The mean estimate of SI change was higher with DCP than with LPS or dLPS but the variability rendered non‐significance. It has been suggested that increased screw purchase can be obtained by engaging the sacrum through the ilium when applying a lateral bone plate in dogs, especially after pelvic osteotomy . Increased bone purchase might lead to less pelvic canal narrowing.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study supported the findings from previous investigations, which indicate that Mg-cement is a biocompatible bone cement that can considerably improve bone-implant interface bonding and induce osteogenesis Data are reported as mean  SEM (based on 16 screws in each treatment group). [5][6][7] Indeed, in our study, 2 screws backed out of their locations after day 5 and probably at day 7 when swelling over the screws was detected. a For this variable, the value for Mg-cement-treated screws is significantly (P  0.05) different from the value for untreated and Ca-cement-treated screws.…”
Section: Discussionmentioning
confidence: 75%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The holding power of an implant in bone is associated with multiple factors such as the mechanical and structural properties of the implant, mechanical and physical properties of the bone, placement of the Influence of bone cements on bone-screw interfaces in the third metacarpal and third metatarsal bones of horses implant, load distribution, and bone-implant integration. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The holding power of an implant in bone is associated with multiple factors such as the mechanical and structural properties of the implant, mechanical and physical properties of the bone, placement of the Influence of bone cements on bone-screw interfaces in the third metacarpal and third metatarsal bones of horses implant, load distribution, and bone-implant integration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, interfragmentary compression achieved with DCP constructs may also accelerate healing. This fracture model also does not account for potentially improved screw purchase with engaging the sacral wing, which has been studied previously with conflicting results [9, 10]. …”
Section: Discussionmentioning
confidence: 99%